Faktor-faktor yang mempengaruhi struktur modal pada bank umum syariah - Rofi’atun, Rofi’atun; Nabila, Rifda (Nur Science Institute, 2021)
This study aims to analyze the effect of institutional ownership, tangibility, profitability, and liquidity on a capital structure with company size as a moderating variable. The type of this study is descriptive quantitative research using secondary data. The population in this study amounted to 14 sharia commercial banks, 10 sharia commercial banks were used as research samples obtained by using a purposive sampling technique. The results of this study indicate that profitability has a significant effect on capital structure. While the institutional ownership, tangibility, and liquidity has no effect on capital structure. Company size is able to moderate the relationship between institutional ownership and profitability on capital structure. However, company size is unable to moderate the relationship between tangibility and liquidity on capital structure.